2019
DOI: 10.1080/14658011.2019.1606580
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of aluminium hypophosphite on the flame retardancy and thermal degradation behaviours of a novel intumescent flame retardant thermoplastic vulcanisate composite

Abstract: The synergistic effects of aluminum hypophosphite (AHP) on the flame retardancy, thermal degradation behaviors of a novel intumescent flame retardant thermoplastic vulcanizate (TPV/IFR) composite were investigated. The results showed that the combination of AHP with IFR showed evident synergistic effects on the increase in the LOI value and reduction of the combustion parameters for the TPV/IFR/AHP composites at the optimum weight ratio of IFR/ AHP (6/1) as evidenced by LOI, UL-94 and CCT. The TGA data reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…27 AHP is usually combined with other flame retardants to obtain better flame retardant performance. [28][29][30][31] Zhou et al 32 added AHP and phosphate tailings (PT) into TPU to enhance fire performance of TPU composites. The results confirmed that the peak heat release rate (PHRR), total heat release rate (THRR) and peak smoke production rate (P-SPR) of TPU/AHP22.5/PT2.5 were 91.2%, 69.9%, and 50.9% decreased compared with those of pure TPU, indicating excellent fire retarding performance of AHP/PT synergistic system.…”
Section: Thermal Decomposition Products Of Ahp Can Promotementioning
confidence: 99%
“…27 AHP is usually combined with other flame retardants to obtain better flame retardant performance. [28][29][30][31] Zhou et al 32 added AHP and phosphate tailings (PT) into TPU to enhance fire performance of TPU composites. The results confirmed that the peak heat release rate (PHRR), total heat release rate (THRR) and peak smoke production rate (P-SPR) of TPU/AHP22.5/PT2.5 were 91.2%, 69.9%, and 50.9% decreased compared with those of pure TPU, indicating excellent fire retarding performance of AHP/PT synergistic system.…”
Section: Thermal Decomposition Products Of Ahp Can Promotementioning
confidence: 99%
“…6, according to Doyle's proposal (Doyle 1961), the thermal degradation curve images of uncoated and coated cotton materials in nitrogen and air are divided into three different areas for the purpose of calculating integral procedural decomposition temperature (IPDT). IPDT is related to the volatile chemical composition of material and can be applied to identify the overall inherent thermal stability of sample at high temperature (Fan et al 2019;Park and Kim 2001), and its value is computed using the following formula:…”
Section: Tg Analysis Of Uncoated and Coated Cotton Materialsmentioning
confidence: 99%
“…In the condensed phase, the phosphorus element in coating sample decomposes into small molecular compounds containing P-OH groups at a lower temperature (Zhang et al 2020). As the temperature rises, the phosphorus-containing components of these small molecules further decompose to produce polyphosphoric acid compounds (Fan et al 2019). Finally, the phosphorus-containing components and cotton cellulose promote the formation of char layer through esterification, crosslinking and other chemical reactions at high temperatures.…”
Section: Flame-retardant Mechanism Research Of Coated Cotton Materialsmentioning
confidence: 99%
“…Besides, much more efforts have been devoted to experimenting with many novel functional additives for combustion suppression as well, such as nano‐boehmite, 21 surface modified montmorillonite, 22,23 graphene oxide, 24,25 attapulgite, 26 and steel slag waste 27,28 . By contrast, as a new type of flame retardant with high phosphorus content, aluminum hypophosphite (AHP) has been given more preference and proved well to be a quite excellent flame retardant, 29–33 especially synergistically compounding with the nitrogen‐based melamine cyanurate (MC), which could significantly improve the flame retardance for various polymer‐based composites, according to many published related papers. For instance, Zhao et al 34 reported that the fire performance of polypropylene (PP)/wood flour (WF) composite could be significantly enhanced based on the 20 wt% addition of AHP/MC with the mass ratio about 5:1, and the UL‐94 achieved V‐0 rating and LOI value increased to 29.5% dramatically.…”
Section: Introductionmentioning
confidence: 99%